1990
DOI: 10.1111/j.1432-1033.1990.tb15351.x
|View full text |Cite
|
Sign up to set email alerts
|

Dictyopterin, 6‐(dthreo‐1,2‐dihydroxypropyl)‐pterin, a new natural isomer of l‐biopterin

Abstract: A major pterin was isolated by reverse-phase high-performance liquid chromatography from cellular extract of vegetative cells of Dictyostelium discoideum after perchloric deproteinization and oxidation with acidic iodine. This compound was characterized by its chromatographic behavior, its absorption and fluorescence properties, by its oxidation product with alkaline permanganate, by secondary ion mass spectrometry and by circular dichroism. The final identification was obtained by comparison with authentic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Whether it is produced by the same cells that express Ga4 or by another cell type is not known. Interestingly, Klein and co-workers have purified a newly discovered pterin, dictyopterin, from vegetative cells that has a structure very similar to monapterin (37). Consistent with our proposal that an endogenous folate or pterin is an essential signaling molecule, we note that D. discoideum expresses an extracellular folate deaminase during the multicellular stages (38) that would have the function of clearing the morphogen from the extracellular space or act as a sink for establishing a possible morphogen gradient within the organism.…”
Section: G4-expressing Cefls Function As Essential Sag Cellsmentioning
confidence: 99%
“…Whether it is produced by the same cells that express Ga4 or by another cell type is not known. Interestingly, Klein and co-workers have purified a newly discovered pterin, dictyopterin, from vegetative cells that has a structure very similar to monapterin (37). Consistent with our proposal that an endogenous folate or pterin is an essential signaling molecule, we note that D. discoideum expresses an extracellular folate deaminase during the multicellular stages (38) that would have the function of clearing the morphogen from the extracellular space or act as a sink for establishing a possible morphogen gradient within the organism.…”
Section: G4-expressing Cefls Function As Essential Sag Cellsmentioning
confidence: 99%
“…Up to now, DH 4 was only identified from vegetative cells of D. discoideum [11]. So, it will be still interesting to know that other DHPRs could also catalyze the conversion of q-DH 2 into DH 4 .…”
Section: Q-dh 2 Catalysis By Rat Dhprmentioning
confidence: 99%
“…BH 4 not only exists in eukaryotes including mammals [6,7], but also in some bacteria as glycosides [8][9][10]. BH 4 is the most common form, but other stereoisomers such as D-threo-BH 4 (tetrahydrodictyopterin, DH 4 ) from Dictyostelium discoideum [11] and L-threo-BH 4 from Chlorobium tepidum [12] have also been detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a pteridine from cell extracts of D. discoideum was identified as 6-(-threo-1,2-dihydroxypropylpterin) (see Figure 1). It was named dictyopterin and represents a new naturally occurring isomer of -biopterin [28]. It was also shown that dictyopterin is deaminated by an extracellular pterin deaminase to -threo-1,2-dihydroxypropyl lumazine (-dictyolumazine) [29].…”
Section: Introductionmentioning
confidence: 99%